Identity, equality, and education - Cerletti, Alejandro (Universidad Pedagógica y Tecnológica de Colombia, 2013)
our current world introduces itself as a unique and omnipresent world: the world of the globalized capitalism in which all the relationships, to a greater or lesser extent, have been commercialized, and everything (products and information) can arrive to every corner of the planet. diversity is accepted as one more element of the (commercial or cultural) merchandise’s circulation, and fits a homogeneous frame in which everything has an allocated place. some contributions from alain badiou are employed in this work in order to deal with this matter, trying to show its constitutive scheme, and to offer some alternative perspectives. the main interest is to display the possibility of thinking a world that makes space to all the possible worlds, and not a world that is the result of the mere planetary subjugation to the expansion of the capital, nor the simple “tolerant” acceptance of the “other”. the link among humans’ conception will be the basis to re-think the education matter in today’s world.